The contributions of language and inhibitory control to false belief reasoning over time - de Villiers, Jill G.; de Villiers, Peter (Frontiers in Psychology, 2025)
IntroductionThe role of language in false belief reasoning has been much debated for twenty-five years or more, especially the relative contributions of general language development, complement syntax, vocabulary, and executive function. However, the empirical studies so far have fallen short, in that they generally have too few participants for adequate statistical modeling; they do not include control variables; or they are cross-sectional rather than longitudinal, making inferences about causal direction much more tenuous.MethodsThe present study considers the role of these different variables in the development of false belief reasoning over several months of testing, with 258 children aged three to five years. The children are also from under-resourced communities, broadening the populations that generally contribute such data.ResultsA cross-sectional and a longitudinal regression analysis reveals the contribution of each variable to the children’s success on the false belief measures. Finally, a structural equation model tests the relative contribution of the different potential factors over time, how they interact, and change. The model is an excellent fit to the data. Inhibitory control, complement comprehension and vocabulary all have effects on false belief reasoning at the first time point (T1). However, at T3, the major proximal contribution is the child’s comprehension of complements, though the longitudinal pathways of vocabulary and inhibitory control also pave the way.DiscussionOur data confirm the specific contribution of complement syntax but also makes clear, as do training studies, that a certain amount of preparedness in vocabulary and in executive function skills is also necessary.